(untitled) (Revista Internacional de Folkcomunicação, 2020)
This article presents a reflection on the informational truth in the testimonies of participants in the “Renovação Carismática Católica do Brasil”. The reports were collected in the preachings of the “Grupo de Oração São José”, where about thirty people meet every Monday at 7:00 pm in the chapel “Nossa Senhora das Graças”, located in the Bateias, neighborhood of the municipality of Gaspar, in Santa Catarina State. The research is based on the perspective of folkcommunication, a theory created by Luiz Beltrão and that speaks of the popular media and its agents. It is analyzed how the testimonies can add informative content to the charismatic community, in the meetings of prayer. Transformations of the social forms of knowledge about reality are also witnessed, hardly contemplated by the traditional journalistic approach. The present research presents, therefore, a framework with the objective of analyzing the collected testimonies. Testimony; Information; RCC; Folkcommunication; Prayer group. Este artículo presenta una reflexión sobre la verdad informativa en los testemonios de los participantes del movimiento religioso “Renovação Carismática Católica do Brasil”.